2021
DOI: 10.1186/s12911-021-01405-0
|View full text |Cite
|
Sign up to set email alerts
|

Designing a national model for assessment of nursing informatics competency

Abstract: Background Due to the need for informatics competencies in the field of nursing, the present study was conducted to design a psychometric instrument to determine the qualification of informatics competencies of employed nurses in educational care centers. Methods The questionnaire was made by reviewing existing scientific resources and assessment tools. Two hundred nurses were selected using simple random sampling. Structural equation modeling was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
1
11
0
1
Order By: Relevance
“…A HIMSS study used the Staggers computer experience questionnaire to query a group of nurses on their basic computer skills, informatics knowledge, and informatics skills 19,20. The study found the majority of nurses reporting few capabilities with informatics competencies, and more than 60% reported low competency with basic computer skills 19. Nurses in a technology-rich environment who don't possess basic technology skills will find themselves frustrated as they try to provide care.…”
Section: Job Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A HIMSS study used the Staggers computer experience questionnaire to query a group of nurses on their basic computer skills, informatics knowledge, and informatics skills 19,20. The study found the majority of nurses reporting few capabilities with informatics competencies, and more than 60% reported low competency with basic computer skills 19. Nurses in a technology-rich environment who don't possess basic technology skills will find themselves frustrated as they try to provide care.…”
Section: Job Descriptionsmentioning
confidence: 99%
“…17 ° The repository of informatics competency-related material on the Healthcare Information and Management Systems Society (HIMSS) website. 18…”
Section: Suggestions For Clinical Laddersmentioning
confidence: 99%
“…At the same time, as the literature has shown, IT still cannot be used effectively in all nursing interventions and by nurses of all ages and specialties. 4,6,7 Previous studies that related to informatics have been limited to nurses' competency and focused on competency in using e-health devices, applied computer skills, and knowledge, [8][9][10][11][12][13][14][15][16][17][18][19][20] perceptions and attitudes of nurses, and so forth; however, no study has focused specifically on the utilization of IT. [21][22][23][24][25][26][27] The literature reviews cited above outlined the most important and widely discussed factors.…”
Section: Introductionmentioning
confidence: 99%
“…Nursing students were found to be more competent in basic computer skills such as searching the Internet, word processing, systems-operations skills, and graphical, and multimedia presentation, but less in applied computer skills and clinical informatics, such as extracting information from clinical data sets, or seeking available resources to help ethical decisions in computing [8]. Additionally, knowledge and skills regarding data analysis and information management needs to be increased [9]. Even in medical school curricula, research has shown differing levels of information literacy competencies and skills among rst-and second-year medical students, requiring the need for progress in informatics competencies [10].…”
Section: Introductionmentioning
confidence: 99%